Taking Stock, June 2010 : An Update on Vietnam's Recent Economic Development - Dinh, Viet Tuan; Rama, Martin (World Bank, Hanoi, 2017)
Vietnam has navigated the global crisis better than many other countries. GDP grew by 5.3 percent in 2009, accelerating to 6.9 percent in the last quarter of the year. At 5.8 percent, the figure for the first quarter of 2010 was less impressive, but claims that growth has slowed down are most probably unwarranted. Exports declined in 2009, for the first time since the beginning of economic reforms, but their decline was smaller than in other countries of the region. By now export growth is converging back to the 30 percent annual growth rate observed before the crisis. Inflation, which had reached 19.9 percent in 2008, was down to 6.5 percent in 2009. While there were some worrying signs of inflation acceleration in late 2009 and early 2010, by now the monthly increase of the Consumer Price Index (CPI) is again moderate. And as in previous years, there were no banking crises despite the continuation of macroeconomic turbulence. More generally, lack of clarity by markets forces the government to overshoot in its policy reactions. Because markets are not sure to understand what the government is up to, they need to see very strong action in order to be convinced that the right course of action has been taken. As a result, Vietnam has had to go through dramatic shifts in the policy stance as circumstances changed. The stabilization policies of 2008 effectively 'killed' the real estate bubble and brought inflation rates to zero in just a few months, but such speed took a toll on economic activity. The stimulus policies of 2009 were equally strong and determined, but they ended up putting too much pressure on international reserves. With more information disclosure and better communication, policy shifts could perhaps be less extreme. Combined with stronger macroeconomic management, it should be possible for Vietnam to gradually free itself from the 'stop-and-go' cycle that has characterized macroeconomic policies over the last three years.